2008
DOI: 10.1080/08959420802050967
|View full text |Cite
|
Sign up to set email alerts
|

Least Restrictive or Least Understood? Waist Restraints, Provider Practices, and Risk of Harm

Abstract: Since implementation of The Omnibus Budget Reconciliation Act of 1987, restraint use in American nursing homes has reduced dramatically. The reduction in vest restraints has resulted in an increase in "least restrictive" devices such as waist restraints. Although this analysis of U.S. Food and Drug Administration Adverse Event Reporting Data Files found that waist devices pose the same potential risk for asphyxial death as vest restraints, few health professionals and consumers are aware of this outcome. Post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among the subgroups most at risk of being submitted to restraint practices were elderly individuals with dementia disorders, particularly in relation to the behavioral manifestations related to their underlying neurological disorder. 8,12,19 It is believed that specific legislation is necessary to reduce the use of mechanical containment, but a study in Japan concluded that the legislation did not contribute in any significant way to the abolition of containment practice in the country. 7 It is revealed, on the other hand, the existence of a specific law in the United States since 1987 which prohibited the use of means of containment and effectively contributed to the progressive reduction of this practice in successive decades.…”
Section: Ghinescumentioning
confidence: 99%
See 1 more Smart Citation
“…Among the subgroups most at risk of being submitted to restraint practices were elderly individuals with dementia disorders, particularly in relation to the behavioral manifestations related to their underlying neurological disorder. 8,12,19 It is believed that specific legislation is necessary to reduce the use of mechanical containment, but a study in Japan concluded that the legislation did not contribute in any significant way to the abolition of containment practice in the country. 7 It is revealed, on the other hand, the existence of a specific law in the United States since 1987 which prohibited the use of means of containment and effectively contributed to the progressive reduction of this practice in successive decades.…”
Section: Ghinescumentioning
confidence: 99%
“…7 It is revealed, on the other hand, the existence of a specific law in the United States since 1987 which prohibited the use of means of containment and effectively contributed to the progressive reduction of this practice in successive decades. 8 It is suggested, in the considerations presented by the authors in a study that compares the practice of mechanical and pharmacological containment, that the variability of the identified results may be related to the absence of specific legislation or standards of standardization of care quality in the two evaluated regions. In any case, the possibility of a direct relationship between the use of restraint, whether mechanical or pharmacological, and the individual characteristics of the guests of long-term institutions evaluated.…”
Section: Ghinescumentioning
confidence: 99%
“…, Capezuti et al . , Saarnio & Isola , Heeren et al . ), our study shows a low level of use of physical restraint (Testad et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, call bells may not be appropriate for all residents, and the bed in the lowest position might actually increase fall risk. 22 Individualized care planning approaches to preventing falls likely needs to be a component of a falls prevention strategy. 20 Such plans require a valid and reliable risk assessment tool that can be used to identify the individual risk profiles on which to match tailored prevention strategies.…”
Section: Discussionmentioning
confidence: 99%